First Round Observation On Increased Micronuclei Frequency Among Rheumatoid Arthritis Patients - SUMITRA M. PITHAWALA; RITA N. MEENA; MEONIS A. PITHAWALA (International Journal of Pharma and Bio Sciences, 2012)
This study was carried out to assess: i) The spontaneous frequency of cytogenetic damage in lymphocytes of rheumatoid arthritis patients using the Cytokinesis blocked micronucleus assay (CBMN) and ii) To know whether DNA damage occur in rheumatoid patients. Cytokinesis blocked micronucleus assay was performed on cultured peripheral blood lymphocytes of 25 rheumatoid arthritis patients and frequency of micronuclei were compared with 25 age/sex and socioeconomically matched control individuals. The results of the present study revealed that there was statistically significant (P<0.05) increase in total micronuclei of rheumatoid patients as compared to control. There was no significant change in the number of apoptotic and necrotic cells among RA patients as compared to the control. However, cells with nuclear buds and nucleoplasmic bridges predominated significantly (P<0.05) in rheumatoid patients as compared to controls. As assessed by CBMN assay DNA damage occurs in rheumatoid arthritis patients.